2011
DOI: 10.4104/pcrj.2010.00064
|View full text |Cite
|
Sign up to set email alerts
|

Management of rhinosinusitis in Dutch general practice

Abstract: Aims: To determine whether general practitioners (GPs) distinguish between the management of acute rhinosinusitis (ARS) and chronic rhinosinusitis (CRS), especially with regard to prescription of antibiotics and nasal steroids.Methods: A questionnaire on the management of rhinosinusitis was sent to 1000 GPs in the Netherlands.Results: Ninety-six percent discriminated between ARS and CRS. However, the definition of ARS and CRS varied. The percentage of GPs prescribing antibiotics rose as rhinosinusitis severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 18 publications
0
21
0
7
Order By: Relevance
“…15 The use of decongestants was approximately three times more common than in our study, which is interesting as the evidence level is low for the efficacy of decongestants in mild to moderate disease. 4,5 However, only one-third of the GPs in the Dutch study considered prescribing intranasal corticosteroids in mild or moderate acute rhinosinusitis.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 42%
See 2 more Smart Citations
“…15 The use of decongestants was approximately three times more common than in our study, which is interesting as the evidence level is low for the efficacy of decongestants in mild to moderate disease. 4,5 However, only one-third of the GPs in the Dutch study considered prescribing intranasal corticosteroids in mild or moderate acute rhinosinusitis.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 42%
“…A recent study performed in the Netherlands using questionnaires sent to GPs showed that oral antibiotics were prescribed by approximately one-third of the practitioners for mild and moderate acute rhinosinusitis. 15 In the current study, we found that antibiotic treatment was common, despite national programmes to reduce its use. 20 The most recent Cochrane update emphasised that antibiotics have a limited treatment effect in acute rhinosinusitis and stated that most cases will resolve without antibiotics within 2 weeks.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 63%
See 1 more Smart Citation
“…Viruses cause most ARS, but discriminating between viral and bacterial rhinosinusitis is challenging and impossible in daily practice. In consequence, too many patients with ARS receive antibiotics [1][2][3]. Expert consensus guidelines recommend antibiotics only for patients with severe symptoms persisting for 10 days or more or for worsening of symptoms after initial improvement [4,5,1].…”
Section: Introductionmentioning
confidence: 99%
“…Среди женщин она была выше, чем среди мужчин, -2 310 против 1 440 на 100 000 населения. У большинства пациентов, вошедших в исследование (69,0%), был зарегистрирован один эпи-зод риносинусита, у 19,0% -один рецидив и лишь у 12,0% -2 и более [14].…”
unclassified